2022
DOI: 10.1021/acsami.2c00753
|View full text |Cite
|
Sign up to set email alerts
|

Lithium Nafion–Modified Li6.05Ga0.25La3Zr2O11.8F0.2 Trilayer Hybrid Solid Electrolyte for High-Voltage Cathodes in All-Solid-State Lithium-Metal Batteries

Abstract: All-solid-state batteries containing ceramic–polymer solid electrolytes are possible alternatives to lithium-metal batteries containing liquid electrolytes in terms of their safety, energy storage, and stability at elevated temperatures. In this study we prepared a garnet-type Li6.05Ga0.25La3Zr2O11.8F0.2 (LGLZOF) solid electrolyte modified with lithium Nafion (LiNf) and incorporated it into poly­(vinylidene fluoride-co-hexafluoropropylene) (PVDF-HFP) matrixes. We used a solution-casting method to obtain bilaye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 45 publications
0
17
0
Order By: Relevance
“…(a) Voltage profiles of the lithium plating/stripping curves of Li/Li symmetrical cells with the PVDF–PZT CPE, PVDF SPE, and PVDF-Al 2 O 3 CPE at a current density of 0.1 mA cm –2 and 25 °C. (b) Comparison of the cycling time of Li/PVDF–PZT CPE/Li symmetrical cells at 25 °C with those of the Li/PVDF-based CPE/Li symmetrical cells reported in the literature. ,, SEM images of the cycled Li surface from Li/PVDF–PZT CPE/Li and Li/PVDF SPE/Li symmetrical cells at current densities of (c) 0.05 mA cm –2 , (d) 0.1 mA cm –2 , and (e) 0.2 mA cm –2 , respectively. (f) C 1s, (g) F 1s, and (h) S 2p XPS spectra of cycled Li anodes from Li/PVDF–PZT CPE/Li and Li/PVDF SPE/Li symmetrical cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(a) Voltage profiles of the lithium plating/stripping curves of Li/Li symmetrical cells with the PVDF–PZT CPE, PVDF SPE, and PVDF-Al 2 O 3 CPE at a current density of 0.1 mA cm –2 and 25 °C. (b) Comparison of the cycling time of Li/PVDF–PZT CPE/Li symmetrical cells at 25 °C with those of the Li/PVDF-based CPE/Li symmetrical cells reported in the literature. ,, SEM images of the cycled Li surface from Li/PVDF–PZT CPE/Li and Li/PVDF SPE/Li symmetrical cells at current densities of (c) 0.05 mA cm –2 , (d) 0.1 mA cm –2 , and (e) 0.2 mA cm –2 , respectively. (f) C 1s, (g) F 1s, and (h) S 2p XPS spectra of cycled Li anodes from Li/PVDF–PZT CPE/Li and Li/PVDF SPE/Li symmetrical cells.…”
Section: Resultsmentioning
confidence: 99%
“…(d) Charge/discharge curves of PVDF–PZT CPE full cells during rate capacities. (e) Cycling performances of NCM811//Li cells with the PVDF–PZT CPE and PVDF SPE full cells at 0.5 C. Charge/discharge curves of the (f) PVDF–PZT CPE and (g) PVDF SPE full cells at 0.5 C. (h) Comparison of the long cycling performance of NCM811/PVDF–PZT CPE/Li cells at 25 °C with reported PVDF-based CPE cells reported in the literature. ,,,, …”
Section: Resultsmentioning
confidence: 99%
“…A garnet-type Li 6.05 Ga 0.25 La 3 Zr 2 O 11.8 F 0.2 (LGLZOF) solid electrolyte modified with lithium Nafion (LiNf) exhibited a superior Li transference number of 0.87, with a capacity retention of 85.1% after 450 cycles in a full cell. One wt % LiNf@f-MWCNT polymer matrix when coated to the side of the electrolyte facing the Li anode is expected to suppress Li dendrite formation, providing a higher Coulombic efficiency of 99.6% . In another study, three-dimensional (3D) interconnected c-LALZO framework not only enabled one to suppress dendrite but also improved the upper limit voltage up to 4.5 V .…”
Section: Approaches To Suppress Lithium Dendrites Penetrationmentioning
confidence: 99%
“…Upon implementation of such composite polymer electrolytes (CPEs), new Li + transport pathways are theoretically accessible either due to Li + transport through the bulk ceramic or at the interface between polymer and ceramic domains. Note that especially the latter is considered to afford highly conductive Li + transport. , However, preferential Li + pathways may be affected by interactions with the polymer matrix, ceramic composition and content as well as the presence of additional plasticizer/mobilizer agents . A synergistic effect combining plasticizers such as tetraglyme or PC with ceramics within a CPE recently demonstrated a boosted Li + conductivity, though sufficient long-term cycling in full cells was missing, rendering further works necessary. , In addition to a homogenous distribution of ceramic particles within the polymer matrix, CIP materials can be designed as layered or gradient structures. A ceramic-rich layer at the Li metal electrode may regulate Li + flux during deposition, even at a capacity utilization of 15 mAh cm –2 , or form a layer with ultrahigh mechanical strength to mitigate Li dendrite growth . Zhu et al showed that a BaTiO 3 -rich layer electrospun at the cathode generates a protective film and stabilizes the interphase .…”
Section: Introductionmentioning
confidence: 99%
“… 27 , 28 In addition to a homogenous distribution of ceramic particles within the polymer matrix, CIP materials can be designed as layered or gradient structures. 29 32 A ceramic-rich layer at the Li metal electrode may regulate Li + flux during deposition, even at a capacity utilization of 15 mAh cm –2 , 30 or form a layer with ultrahigh mechanical strength to mitigate Li dendrite growth. 31 Zhu et al showed that a BaTiO 3 -rich layer electrospun at the cathode generates a protective film and stabilizes the interphase.…”
Section: Introductionmentioning
confidence: 99%